Associations of cannabis retail outlet availability and neighborhood disadvantage with cannabis use and related risk factors among young adults in Washington State. (1st March 2022) - Rhew, Isaac C.; Guttmannova, Katarina; Kilmer, Jason R.; Fleming, Charles B.; Hultgren, Brittney A.; Hurvitz, Philip M.; Dilley, Julia A.; Larimer, Mary E.
Abstract: Background: This study examined associations of local cannabis retail outlet availability and neighborhood disadvantage with cannabis use and related risk factors among young adults. Methods: Data were from annual cross-sectional surveys administered from 2015 to 2019 to individuals ages 18–25 residing in Washington State (N = 10, 009). As outcomes, this study assessed self-reported cannabis use at different margins/frequencies (any past year, at least monthly, at least weekly, at least daily) and perceived ease of access to cannabis and acceptability of cannabis use in the community. Cannabis retail outlet availability was defined as the presence of at least one retail outlet within a 1-kilometer road network buffer of one's residence. S ensitivity analyses explored four other spatial metrics to define outlet availability (any outlet within 0.5-km, 2-km, and the census tract; and census tract density per 1000 residents). Census tract level disadvantage was a composite of five US census variables. Results: Adjusting for individual- and area-level covariates, living within 1-kilometer of at least one cannabis retail outlet was statistically significantly associated with any past year and at least monthly cannabis use as well as high perceived access to cannabis. Results using a 2-km buffer and census tract-level metrics for retail outlet availability showed similar findings. Neighborhood disadvantage was statistically significantly associated with at least weekly and at least daily cannabis use and with greater perceived acceptability of cannabis use. Conclusions: Results may have implications for regulatory and prevention strategies to reduce the population burden of cannabis use and related harms. Highlights: This study examined impacts of local area-level factors on cannabis use in young adults. Cannabis retail outlet availability was associated with any past year and at least monthly cannabis use. Perceived access to cannabis was higher among those living near cannabis retail outlets. Neighborhood disadvantage was associated with cannabis use and perceived acceptability. Area-level prevention strategies may be warranted to reduce cannabis-related harms.